Dynamic characterization of flexible vibrating structures using Adaptive Neuro-fuzzy Inference System (ANFIS) - Ismail, A. Y.; Ismail, R.; Mat Darus, I. Z (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org